The Effect Of Motivation And Family Support For Students Learning Achievement Level Ii Prodi D-III Midwifery Stikes Ubudiyah Banda Aceh - Safitri, Faradilla (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Learning achievement is the human level of the students in accepting, rejecting, and assess the information obtained in the learning process. The are many factors many factors that influence the success process in the learning, such as learning motivation and family support. Students motivation become a low, so the quality of achievement will be low. Therefore, the quality of the students learning achievement needs to be increased continuously in order for students to have a strong motivation to learn, so that the learning performance can be achieved optimally. In their family students needed theÂ  support of their parents in achieving learning achievement, because the support and attention will determine the students reached aÂ  high academic achievement. The purpose of this study was to determine the "influence of motivation and family support on student achievement level II Prodi D-III Midwifery STIKes UBudiyah Banda Aceh". This research is analytic with cross sectional approach. The population in this study were all second level students Prodi D-III Midwifery, amounting to 73 people. The sampling technique total sampling with criteria entire second level students are active in the fourth semester of the academic year 2012/2013 is 73 people. The research instrument used questionnaires and transcripts. This study was conducted on 20 August to 24 August, 2013. The results of this analysis study showed that there is influence of motivation on student achievement in grades P-Value = 0.000 (P <0.05) and no family support influences on student achievement in grades P-Value = 0.000 (P <0.05) . Based on the results of this study concluded that there was a significant relationship between motivation and family support on student achievement. Expected as input to the students and families that motivation and family support plays an important role in improving student achievement.